Wildlife governance in an era of social change: how science, politics, and culture influence conservation governance - Sullivan, Leeann Marie, author; Manfredo, Michael, advisor; Teel, Tara, advisor; Gruby, Rebecca, committee member; McIvor, David, committee member (Colorado State University. Libraries, 2020)
Wildlife conservation faces unprecedented ecological challenges in the years ahead. But it is the human dimensions of conservation, from competing values to inequities in access to power, that pose the most significant threat to these efforts in the near term. As values toward wildlife shift in response to modernization and more people become engaged in political activism around conservation issues, wildlife organizations in the public and non-profit sector face calls for governance reform to bring a broader diversity of the public into conservation efforts. Such inclusive and pluralistic models of conservation governance, however, mark a significant divergence from technocratic approaches of the past that prioritize input from technically trained experts over members of the public and root almost exclusively in domination ideologies. The resulting conflict between wildlife conservation centered on science and expertise and the democratic belief that all people should have a say in the management and protection of their natural resources marks a significant contradiction at the heart of wildlife conservation. Assessing the potential for achieving more participatory conservation within this frame requires a deeper understanding of the cultural, social, and political drivers of technocratic governance and how both internal and external factors serve to reinforce these political practices. In this dissertation, I draw out the historical, institutional, and cultural foundations of technocracy in wildlife conservation and their implications for achieving a participatory turn. In Chapter 2, I outline how historic paradigms for scientific expertise and domination values in U.S. wildlife management shapes the frame through which practitioners perceive their organizations as adaptable and accountable and ultimately influence perceptions of the need for change. In Chapters 3 and 4, I explore how existing governance modes are culturally reinforced, first through an internal "technocratic mentality" which proposes that scientifically-trained experts are solely and uniquely qualified to make decisions about wildlife and second, through external cultural pressures that influence governance processes in response to broader societal pressures for hierarchy and social order. Taken together, these chapters illustrate the complex and socially embedded nature of power in wildlife conservation and offer new insight into the potential for achieving governance reform in an era of social change.
Keywords: modernization; technocracy; governance; wildlife; participation